SURVEY ON THE DIVERSITY OF PREDATORY MITES (FAMILY : PHYTOSEIIDAE) ON MEDICINAL PLANTS IN KOZHIKODE AND WAYANAD DISTRICTS OF KERALA, INDIA - SADANANDAN, MARY ANITHALATHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The Phytoseiid mites harbouring various species of medicinal plants were collected by making extensive survey in Kozhikode and Wayanad districts of Kerala during a period of 9 months i.e. from April 2014 to December 2014. The survey yielded 11 species of predatory mites belonging to 3 genera vi:. Amblyseius, Eusieus and Neoseiulus under the suborder Mesostigmata.